2016
DOI: 10.1101/078220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the Relationship Between Vegetation Structure and Harvestmen Assemblage in an Amazonian Upland Forest

Abstract: Abstract1. Arthropod diversity and non-flying arthropod food web are strongly influenced by habitat components related to plant architecture and habitat structural complexity. However, we still poorly understand the relationship between arthropod diversity and the vegetation structure at different spatial scales. Here, we examined how harvestmen assemblages are distributed across six local scale habitats (trees, dead trunks, palms, bushes, herbs and litter), and along three proxies of vegetation structure (num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…In the Balbina archipelagic landscape, island size was a strong positive predictor of species richness in other taxonomic groups ─ including birds (Aurélio‐Silva et al ., ), small mammals (Palmeirim et al ., ) and large mammals (Benchimol & Peres, ). Although SAR is one of the few ironclad rules in ecology (Matthews et al ., ), we found that area failed in explaining richness patterns for harvestmen assemblages, the absence of this relationship has been documented before for this group in Amazonian upland forest sites where microhabitat structure and availability per unit area also explained patterns of harvestmen species composition but not species richness in harvestmen assemblages (Colmenares et al ., ). The same pattern was also found for other arthropods, such as macro‐moth communities in temperate woodland countryside landscapes, although in that case habitat amount, rather than patch size and isolation were the main drivers of species richness (Merckx et al ., ), both however have not explained it for harvestmen either.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In the Balbina archipelagic landscape, island size was a strong positive predictor of species richness in other taxonomic groups ─ including birds (Aurélio‐Silva et al ., ), small mammals (Palmeirim et al ., ) and large mammals (Benchimol & Peres, ). Although SAR is one of the few ironclad rules in ecology (Matthews et al ., ), we found that area failed in explaining richness patterns for harvestmen assemblages, the absence of this relationship has been documented before for this group in Amazonian upland forest sites where microhabitat structure and availability per unit area also explained patterns of harvestmen species composition but not species richness in harvestmen assemblages (Colmenares et al ., ). The same pattern was also found for other arthropods, such as macro‐moth communities in temperate woodland countryside landscapes, although in that case habitat amount, rather than patch size and isolation were the main drivers of species richness (Merckx et al ., ), both however have not explained it for harvestmen either.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, this was an important variable structuring both harvestmen species composition and abundance across the Balbina islands. A positive association between harvestmen assemblages and fallen logs has not always been detected in undisturbed tropical forests, but this microhabitat type is often associated with some specific harvestmen species in Amazonian forests (Colmenares et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations